A bio-adhesion nanogel particle as an anti-inflammation agent for efficient aerosol inhalation therapy to asthma - Yi-Bing Chen; Jing-Yi Hou; Xiao-Yue Yue; Yan-Qiu Wang; Jian Huang; Dong Xu; Yuan-Lu Cui; Qiangsong Wang (Materials & Design, 2024)
Asthma is a heterogeneous respiratory disease characterized by airway inflammation occurring in the bronchus. Direct delivery of targeted treatments to the bronchus for asthma has the potential to optimize therapeutic efficacy. Inhaled corticosteroids are cornerstone therapy for persistent asthma, however, there remain challenges in designing effective formulations for the inhaled route and minimizing long-term corticosteroid side effects. Here, a nanogel delivery system with good bio-adhesion based on alginate crosslinked with zinc ions was designed. The prepared alginate nanogel particles (ALG-NPs) effectively delivered icariin (ICA) which possesses anti-inflammatory and antioxidant activities, to the bronchus through ultrasonic aerosol inhalation, thereby ameliorating asthmatic symptoms and attenuating bronchial inflammation. The ALG-NPs exhibited favorable biological safety and could be deposited in the bronchus to control the release of ICA, enabling targeted treatment of asthma. In addition, ICA loaded ALG-NPs significantly reduced airway inflammation by modulating key targets associated with asthm (Th1 transcription factor and Th2 transcription factor) while also inducing eosinophilic apoptosis by regulating the Bax/Bcl-2 ratio expression. This study suggests that the ultrasonic aerosol inhalation of ICA loaded ALG-NPs was a promising strategy of treating asthma.